Високотемпературне дослідження особливостей продувки металевої ванни в LD конвертері через кільцеве коаксіальне сопло - Семикін, С.І.; Голуб, Т.С.; Дудченко, С.О.; Вакульчук, В.В. (Physico-technological Institute of Metals and Alloys, 2023)
The process of interaction of a high-speed gas stream of an oxidizing agent flowing from the top blowing lance during oxygen LD conversion with melt is a determining and decisive factor in the development and occurrence of thermal and exchange processes. The paper presents the results of a high-temperature study of the nature and characteristics of blowing a metal melt through the top lance with an annular coaxial nozzle based on a 60-kg laboratory converter in comparison with the work of four nozzle tips. On the basis of continuous video recording by a high-speed camera with a frequency of 300 frames per second and recording of technological indicators, the nature of the interaction of an oxygen jet with a liquid bath was studied and the conclusions obtained at the “cold” modeling about higher dynamic pressure and deep penetration into the melt of the jet using an experienced tip were confirmed. Earlier ignition of the melting and a significant increase in the temperature of the sublance area recorded by the pyrometer were revealed, probably due to the creation of a zone of intense postcombustion of CO to CO2 in the sub-lance region. However, the deep penetration of the jet led to a more stringent blowing with the formation of a smaller amount of slag, probably due to a smaller intake of iron oxides in the slag than in comparative heat. According to the magnitude of the decrease in the level of carbon in the melt compared to comparative melts at the same level of the amount of oxygen supplied, an increase in the proportion of oxygen spent on carbon oxidation using an experimental tip was found, with a corresponding increase in the rate of carbon oxidation during the blowing.